2007
DOI: 10.1590/s0101-20612007000100019
|View full text |Cite
|
Sign up to set email alerts
|

Antinutrients in the cassava (Manihot esculenta Crantz) leaf powder at three ages of the plant

Abstract: In Brazil, the cassava leaf meal (CLM) has been used to strive against undernourishment because it is a high source of vitamins and minerals. However, the wide variation in the chemical composition of the different cultivars, as well as their antinutritional substances may be a restriction to their uses. The levels of some antinutrients in CLM from five cultivars at three ages of the plant (TAP) were investigated, in order to select the cultivars and plant ages that would be more appropriate for human consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 29 publications
(27 reference statements)
0
49
1
5
Order By: Relevance
“…Nappi et al (2006) analyzed the level of oxalic acid in multimixtures (wheat, maize flour, egg shell, and manioc leaf) and obtained the value of 510 mg. sample kg -1 , an amount smaller than that found in the present study in yacon peel flour (PeF). However, the manioc leaf had high concentration of oxalic acid, between 444 mg.kg -1 and 570 mg.kg -1 of whole matter (WOBETO et al, 2007), which is higher than the levels found for the yacon and derived products in the present study, except for yacon peel flour.…”
Section: Resultscontrasting
confidence: 91%
“…Nappi et al (2006) analyzed the level of oxalic acid in multimixtures (wheat, maize flour, egg shell, and manioc leaf) and obtained the value of 510 mg. sample kg -1 , an amount smaller than that found in the present study in yacon peel flour (PeF). However, the manioc leaf had high concentration of oxalic acid, between 444 mg.kg -1 and 570 mg.kg -1 of whole matter (WOBETO et al, 2007), which is higher than the levels found for the yacon and derived products in the present study, except for yacon peel flour.…”
Section: Resultscontrasting
confidence: 91%
“…Cassava also contains its own share of anti-nutrients, which have either positive or negative efects on the health, depending upon the amount of the component being ingested [21]. They basically interfere with the digestibility and uptake of some nutrients.…”
Section: Nutritive and Anti-nutritive Properties Of Cassavamentioning
confidence: 99%
“…The consumption of lower cyanide amounts is not lethal but long-term intake could cause severe health problems such as tropical neuropathy [22]. The nitrate content in cassava leaves ranges from 43 to 310 mg/100 g DM (dry mater) [21]. Cassava-eating populations are naturally exposed to high amounts of cyanide, nitrates and nitrites-chemical compounds which are known to contribute to the risk of developing stomach cancer [22].…”
Section: Nutritive and Anti-nutritive Properties Of Cassavamentioning
confidence: 99%
See 1 more Smart Citation
“…Porém, seu consumo direto fica limitado pela presença de agentes tóxicos e antinutricionais, como polifenóis (taninos), inibidores da tripsina, saponina, hemaglutinina e cianeto, necessitando passar por processos que reduzam sua concentração, além de reduzir a parte fibrosa, que não é digerida por humanos e animais monogástricos (MELO et al, 2007;MODESTI et al, 2007;WOBETO et al, 2007;TEO et al, 2010).…”
Section: Introductionunclassified